Quercetin-PVP K25 solid dispersions: Preparation, thermal characterization and antioxidant activity - de Mello Costa, Ana Rita; Marquiafavel, Flavia Silva; Lima Leite Vaz, Mirela Mara de Oliveira; Rocha, Bruno Alves; Pires Bueno, Paula Carolina; Amaral, Pedro Luiz M. [UNESP]; Barud, Hernane da Silva; Ap Berreta-Silva, Andresa (Springer, 2011)
Quercetin is a flavonoid very well studied and has already entered clinical trials emerging as prospective anticancer drug candidate. In addition, quercetin has being reported to its free-radical scavenging activity and suggests potential uses for the prevention and treatment of pathologies as atherosclerosis, chronic inflammation, and others. However, quercetin is sparingly soluble in water, which may be responsible for its limited absorption upon oral administration. The solid dispersion of quercetin with polyvinylpyrrolidone Kollidon(A (R)) 25 (PVP K25) suggests an interesting way to increase quercetin solubility, antioxidant activity, and consequently bioavailability. Then, the purpose of this study was to prepare solid dispersions of quercetin with PVP K25 and evaluate their thermal characterization, antioxidant activity and quercetin improvement solubility. For this purpose, quercetin-PVP K25 solutions were dried and quercetin-PVP K25 solids were obtained. The formation of quercetin-PVP K25 solid dispersion was evaluated by solubility studies, powder X-ray diffraction (XRD), fourier transform infrared spectroscopy (FT-IR), differential scanning calorimetry (DSC), thermogravimetry (TG), and antioxidant activity. It was observed that PVP K25 was able to provide quercetin clear aqueous solutions and that quercetin solubility was increased in a PVP K25 concentration dependent manner, improving solubility even 436-fold the pure quercetin. The results obtained with XRD, FT-IR, DSC, and TG demonstrated possible quercetin-PVP K25 solid dispersion formation. Besides, the antioxidant activity of the quercetin-PVP K25 solid dispersions dissolved in aqueous solution and pure quercetin dissolved in methanol showed IC50 value of 0.61 +/- A 0.03 and 1.00 +/- A 0.02 mu g/mL, respectively, demonstrating that the solid dispersions presented a significant increase in antioxidant activity (P < 0.05). Putting results together, it was possible to conclude there was the formation of quercetin-PVP K25 solid dispersion.
Keywords: Quercetin; Polyvinylpyrrolidone; Thermal characterization; Antioxidant activity